Penyesalan Pasca Pembelian Ditinjau dari Big Five Personality - Iskandar, Lila Meutia; Zulkarnain, - (Faculty of Psychology, Universitas Gadjah Mada, 2013)
The purpose of this study is to determine relationship between big five personality dimensions and post purchase regret. The study was done cross sectionally and involving 207 students of University â€œXâ€ at Sumatera Utara. Data was collected through Big Five Inventory (BFI) and Post Purchase Consumer Regret (PPCR) scales. Data was analyzed using Pearson correlation and multiple regressions. The result shows that there is a significant correlation between big five personality and post purchase regret (r=0.374, p